2016
DOI: 10.1002/jhbp.362
|View full text |Cite
|
Sign up to set email alerts
|

Single institution results of radical antegrade modular pancreatosplenectomy for adenocarcinoma of the body and tail of pancreas in 78 patients

Abstract: The RAMPS technique resulted in high negative tangential margin rates and good lymph node retrieval. The long-term survival result in 78 patients is probably an accurate reflection of what is possible with this tumor using this technique at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…In this meta-analysis, we found that the R0 resection rate was significantly higher in the RAMPS group than in the standard surgery group [89.5% vs 83.6%, OR 95% CI, 2.19 (1.16 ~ 4.13); P  = 0.02]. However, the combined resection rates were comparable between the RAMPS and standard groups [OR 95% CI, 3.30 (1.00 ~ 10.93); P  = 0.05], which might be attributable to the low rate of posterior RAMPS procedures in present practices [24, 31, 32]. …”
Section: Discussionmentioning
confidence: 95%
“…In this meta-analysis, we found that the R0 resection rate was significantly higher in the RAMPS group than in the standard surgery group [89.5% vs 83.6%, OR 95% CI, 2.19 (1.16 ~ 4.13); P  = 0.02]. However, the combined resection rates were comparable between the RAMPS and standard groups [OR 95% CI, 3.30 (1.00 ~ 10.93); P  = 0.05], which might be attributable to the low rate of posterior RAMPS procedures in present practices [24, 31, 32]. …”
Section: Discussionmentioning
confidence: 95%
“…It is difficult to evaluate RAMPS in terms of recurrence and overall survival due to high systemic recurrence rates that reach as high as 80% in some studies (2). Advanced local resection techniques cannot elevate five-yearoverall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Until 2003 the preferred approach for this type of lesions was the standard retrograde pancreatosplenectomy (SRPS). Strasberg et al (1) in 2003 were the first who described the Radical Antegrade Modular Pancreatosplenectomy (RAMPS) in order to standardize the way pancreatic tumors of the body and tail should be surgically approached (1,2). It is built based on N1 lymph node dissection, after O'Morchoe's (3) description and classification of the pancreatic lymphatic drainage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After discussion at our multidisciplinary tumor conference, she was taken for radical antegrade modular pancreatosplenectomy in April 2015 [16, 17]. Initially, a diagnostic laparoscopy was performed, which did not demonstrate evidence of disseminated or peritoneal metastasis.…”
Section: Case Reportmentioning
confidence: 99%